Penggunaan Media Digital Paroki Kristus Terang Dunia Waena - Geor, Maria Chrisnayanti; Silitubun, Evaristus (STPK St. Yohanes Rasul Jayapura, 2025)
Digital technology is growing day by day. This development undoubtedly has a significant impact on all aspects of human life worldwide. Therefore, this technological advancement is considered a gift from God. The purpose of this study was to determine the extent of digital media use for evangelization and the supporting and inhibiting factors in its use at the Christ the Light of the World Parish in Waena Jayapura. To achieve these two objectives, the author used qualitative methods, with data collection techniques including observation and interviews with 12 informants. The results revealed that digital media used as a means of evangelization include live streaming, daily reflections Lumen Christi, and catechesis. These media are used as a means of activities open to the public. Supporting factors in evangelization include the availability of adequate digital devices and adequate human resources. Inhibiting factors relate to the digital devices used and the sense of appreciation of media use in evangelization, as the use of digital media is considered new in liturgical celebrations.